Laboratory coagulation tests and recombinant porcine factor VIII: A United Kingdom Haemophilia Centre Doctors' Organisation guideline. Issue 3 (13th March 2022) - Bowyer, Annette; Gray, Elaine; Lowe, Anna; Murphy, Paul; Platton, Sean; Riddell, Anne; Chowdary, Pratima; Lester, Will; Jenkins, Peter Vincent
Abstract: Introduction: Acquired haemophilia A (AHA) is a rare bleeding disorder caused by development of auto‐antibodies to endogenous coagulation factor VIII (FVIII). Recombinant porcine factor VIII (rpFVIII) is currently licensed only for the management of bleeding in patients with AHA. Regular monitoring of rpFVIII is recommended to assess treatment effectiveness. Aim: This guideline from the United Kingdom Haemophilia Centre Doctors' Organisation (UKHCDO) examines the current publications in the area and aims to offer advice for the laboratory monitoring of rpFVIII in patients with AHA. Methods: A review of the current literature was undertaken followed by critical review by the authors. Results/conclusions: A validated one‐stage clotting FVIII assay is recommended for the measurement and regular monitoring of rpFVIII. Assessment of cross‐reacting rpFVIII inhibitors by one‐stage porcine Bethesda assay should be performed as part of the initial diagnosis of AHA or prior to treatment with rpFVIII. Available data show that chromogenic FVIII assays underestimate rpFVIII and this should be considered if measurement of rpFVIII is required in patients receiving Emicizumab.